Acupuncture at Zusanli (ST36) for the benefits of sepsis–laboratory evidence for “preventive treatment of disease” and “holistic concept” in the protective effects of acupuncture: a literature review of rodent studies - Zeng, Lin; Yan, Jiangtian (Frontiers in Neurology, 2025)
The objective of this study was to explore the holistic anti-inflammatory mechanisms of acupuncture at ST36 in sepsis-related multi-organ damage. Current research indicates that ST36 stimulation neuro-endocrine-immune network and serum exosome, which exhibit anti-inflammatory properties in sepsis or normal mice. However, critical gaps persist: Firstly, there is a necessity for further exploration of neural circuit mechanisms, given that the effects of acupuncture involve multiple interdependent pathways [e.g., sympathetic nervous system, vagus nervous system (cholinergic anti-inflammatory pathway and vagal- splanchnic nerve axis)], which underscores the importance of studies on context-specific neural conduction conditions. Secondly, there is a lack of clarity regarding exosome dynamics, including their production mechanisms, cellular origins, and optimal therapeutic targets. The last, while the majority of studies have focused on post-inflammatory regulation, emerging evidence suggests the potential for preventive applications, such as the observation that low-intensity ST36 electroacupuncture activates disease-independent anti-inflammatory pathways. Future research must integrate neural circuit complexity, exosome biology, and preventive applications to advance acupuncture’s translational utility in sepsis and systemic inflammation.